- 1-214-256-5804
- info@tutorpace.com

The following examples clearly illustrate the division of expression with exponents.

To simplify this use rule of exponents

Divide the exponent having like bases; subtract the exponent of variable x in the denominator from the exponent of variable x in the numerator

X^5 / x^-3 = x^5-(-3) = x^5+3 = x^8

And 7/1= 7

Therefore, 7x^5 / x^-3 = 7x^8

x^3 / x^7 = x^3-7 = x^-4

y^2 / y = y^2-1 = y^1=y (note that y = y^1 )

Then z^-5 / z = z^-5-1 = z^ -6

Combine all the terms together, we get 2x^-4yz^-6

This is the required solution.

Multiply the exponent first and then divide by the denominator

So, a^3.a^2 / a^-1 = a^3+2 – (-1) = a^6

15/3 = 5

b^4 / b^2 = b^4-2 = b^2

15a^3b^4a^2 / 3a^-1b^2 = 5 a^6 b^2.